UNDERSTANDING ONLINE MISOGYNY: A FRAMEWORK FOR ANALYZING HATE SPEECH TARGETING WOMEN IN SCHOOLS - Hasan Baharun; thoiful abrar (Marwah: Jurnal Perempuan, Agama dan Jender, 2026)
This study aimed to examine the forms, dynamics, and effects of internet misogyny on women’s engagement in school-based digital and academic spaces. Using a qualitative case study approach, data were collected through in-depth interviews, observation, digital interaction analysis, and review of school records. The data were analyzed through condensation, data presentation, verification, content analysis, and discourse analysis. The findings indicate that internet misogyny appears in various forms, including derogatory language, sexist humor, memes, and digital symbols that reproduce gender stereotypes and normalize the marginalization of women. These practices are reinforced by school-based social and cultural structures, particularly through moral discourses, gendered role distribution, and tolerance toward sexist jokes. The effects include declining self-confidence, digital anxiety, avoidance of academic interaction spaces, and reduced participation of female students in classroom discussions and school organizations. This study implies the need for gender-responsive digital literacy, stronger student protection mechanisms, and the development of a safe, inclusive, and equitable school culture. Keywords: online misogyny, women's participation, school culture